The diaconal role of the roman catholic church within the diocese of Lindi Southern Tanzania : an assessment of its transformational development - Kamwendo, John Francis (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2012.